A gender analysis perspective for improved livelihoods in the Karkheh River basin - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Social survey (quantitative research) and participatory rural appraisal (PRA) (qualitative research) were carried out in a study conducted in Merek (Kermanshah Province) and Honam (Lorestan Province) in Iran. The study aims to find new ways of improving the incomes of rural households, based on the role of women in agricultural production and the division of labor in socioeconomic activities between men and women.